Estudo fitoquímico de Condalia buxifolia reissek: isolamento, determinação estrutural e atividades antimicrobianas - Gehm, Adriana Zambenedetti (2020)
This work describes the phytochemical study of the Condalia buxifolia Reissek species, belonging to the Rhamnaceae family, and evaluation of the antimicrobial potencial of the extracts obtained and of the isolated metabolites for study of the ratio structure/activity. With the methanolic crude extract (EB) of the bark of the roots of Condalia buxifolia, acid-base fractionation was performed, obtaining basic ethereal fraction (FEB) and acidic etheric fraction (FEA). From the FEB a neutral cyclopeptide, scutianene X, five known cyclopeptide alkaloids scutianin B, scutianin D, frangulanine, condaline A and scutianine E were isolated and a new cyclopeptide alkaloid called condaline B. From the FEA, the phytosterols stigmasterol acetylglucoside and sitosterol--D-glucoside and a flavonoid of the catechin class, 4'-O-methyl-gallocatechin were isolated. From the leaves crude extract, a mixture of lupeol and -amirine triterpenes was isolated. In addition, the alkaloid condaline B was obtained synthetically from the transformation of condaline A. This transformation, in addition to confirming the structure, was important to attribute the stereochemistry of condaline B, as being the same of condaline A. The antimicrobial activity test it was carried out by the microdilution in plates method and standard strains of different microorganisms were used: six gram-positive bacterias, ten gram-negative bacterias and nine fungi. Of the cyclopeptide alkaloids, only condaline A and B had their antimicrobial potential evaluated for fungi and demonstrated good MIC against fungi Candida krusei and Cryptococcus gatti. The other alkaloids showed moderate MIC for gram-positive bacteria Staphylococcus aureus and gram-negative bacteria Morganella Morgani. The scutianin D alkaloid showed a good MIC for the gram-negative bacteria Pseudomonas aeroginosa.